A influência da violência doméstica para o cometimento do crime de homicídio pela mulher vítima: um estudo de caso na cidade de Manaus - Macedo, Arthur Sant’anna Ferreira (2023)
Introduction/Importance: Domestic violence affects thousands of women throughout their lives. It is common to observe, through the various forms of news, that women are assaulted, mistreated, abused and killed every day by people in their family life. Some women manage to get rid of the torment of violence through the means made available for their protection, while others make decisions in conflict with the criminal law, but which they understand as effective in getting rid of the context of domestic violence. In this sense, the present research represents a way to understand how the domestic violence suffered transforms a woman victim into the author of the crime of homicide, attempted or consummated. Information and life stories of women perpetrators of the crime of homicide are brought to light to show readers social problems that need to be debated in order to improve the protection of women. Objective: to investigate the influence of domestic violence suffered by women for the commission of the crime of homicide, in the attempted or consummated form, capitulated in article 121 of the Penal Code, but without being under the cloak of any of the exclusions of unlawfulness, such as the self-defense provided for in article 25, caput, of the Penal Code. The study also sought to understand the context and moment of the woman's decision to commit the crime of homicide. Locus: the empirical data were collected at the Manaus Women's Detention Center, where there are women incarcerated and each one with their own particular life story. Methodology: it was used as a case study, of a qualitative nature. The data collection procedures involved secondary sources - bibliographic review, analysis of law and jurisprudence, as well as primary sources - in-depth interviews with these women, in which we sought to verify whether, among the perpetrators of homicide crimes, any committed the crime influenced by domestic violence he was suffering. Results: the data indicated a conflicting reality for these women in aspects of emotional experience, life perspectives, intra-family relationships, in which these women's feelings of anger, fear and guilt stood out. 4 (four) women were heard, all self-declared brown, school life varying between high school and higher education and with family income below 3 minimum wages, who brought their reality to the study and half of the research participants were clear in say that they only committed the crime of homicide to get rid of the domestic violence they had been suffering. Aspects of patriarchy were observed in the participants' speeches, which demonstrates the importance of studying and publicizing the theme to understand the world of female criminality. Conclusion: it was concluded, through the data obtained, that domestic violence is a factor that influences the woman victim to commit the crime of homicide. In view of this, it remains evident to study female criminality from the perspective and reality of women so that effective measures are developed to contain the advance of female criminality and incarceration.